how can i change this string:

"f(x)= x + 2-3\nbox = f(2) + 2\nbox = f(f(2)) + 2\nfunc = 3 + 3 * 4


to:

"box = 1 + 2\nbox = 0 + 2\nfunc = 3 + 3 * 4\n"


or tell me the algorithm to make this happen, i will try to figure it out.....plz, thanks alot, ihave been spending alot of time on this already...

Recommended Answers

All 2 Replies

plz help, waiting anxiously....................

We will only help those who show some effort!
In other words, show us some Python code you have tried to solve your problem.

The problem is real easy to solve, hint ...

# "f(x)= x + 2 - 3" implies the function below

def f(x):
    return x + 2 - 3
Be a part of the DaniWeb community

We're a friendly, industry-focused community of developers, IT pros, digital marketers, and technology enthusiasts meeting, networking, learning, and sharing knowledge.